Comparability of photographic film developer and fixer solutions with radiographic film developer and fixer solutions in radiographic film processing - Gonzales, Joyce Izza Marie G.; Dellosa, Patricia F.; Gonzalez, Ian Timothy P.; Rosanes, Rose Anne D. (Adviser).; Meneses, Michelle Marie Z. (Co-author).
Conventional radiography is still widely used in dental practice, according to Muhamadegic 2009 and Child and Christenses 2010. It is relatively cheaper, requires less training and equipment than digital radiography. However, there are undocumented reports on the use of photographic solutions as substitute to radiographic solutions to make image processing a lot cheaper. This study aimed to test the comparability of image produced in terms of density and contrast. Photographic solutions could be an alternative if proved to be comparable with radiographic solutions. Forty periapical films were exposed from a film cassette with six filters. Twenty were processed with radiographic solutions while the other 20 were processed in photographic solutions, under standardized radiographic film processing. Densities were measured by a densitometer and contrasts were computed through the slope of each characteristic curve made from every film. Based on independent t-test, images procedured by photographic solutions were not comparable to radiographic solutions.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.